Length variants of the ABCB1 3′-UTR and loss of miRNA binding sites: possible consequences in regulation and pharmacotherapy resistance. (March 2016) - Bruhn, Oliver; Drerup, Katharina; Kaehler, Meike; Haenisch, Sierk; Röder, Christian; Cascorbi, Ingolf
Aim: To identify the exact length and possible length variations of the ABCB1 3′-UTR as important regulatory site for miRNA interaction of this drug transporter and its possible contribution to drug resistance.Materials & methods: 3′-RACE and various standard PCR experiments were performed using cDNA of different human cell lines and liver tissue. The abundance of 3′-UTR fragments was analyzed using quantitative RT-PCR.Results: Five different ABCB1 3′-UTR length variants were identified. miRNA binding sites were located only on the three longer fragments. Imatinib-resistant leukemia cells expressed predominantly shorter 3′-UTRs, where miRNA binding sites are absent.Conclusion: Shortening of the ABCB1 3′-UTR causes loss of miRNA-dependent translational control leading to elevated ABCB1 protein levels.